Unveiling Active Constituents and Potential Targets Related to the Hematinic Effect of Steamed Panax notoginseng Using Network Pharmacology Coupled With Multivariate Data Analyses - Xiong, Yin; Hu, Yupiao; Chen, Lijuan; Zhang, Zejun; Zhang, Yiming; Niu, Ming; Cui, Xiuming (Frontiers in Pharmacology, 2019)
To unveil active constituents and potential targets related to the hematinic effect of steamed Panax notoginseng (SPN), a constituent-target-disease network was constructed and multivariate data analyses were performed. According to the results, 11 targets related to chemical constituents of SPN were found to be closely associated with the hematinic effect of SPN. Among them, the direct target protein of mitochondrial ferrochelatase (FECH) had the major role through the metabolic pathway. Meanwhile, Rk3 and 20(S)-Rg3 were predicted to be major constituents related to the hematinic effect of SPN by both multivariate data analyses and network pharmacology. And the pharmacologic tests validated that Rk3 and 20(S)-Rg3 could significantly increase the levels of blood routine parameters, FECH and its downstream protein of heme in mice with blood deficiency syndrome. The study provides evidences for the mechanism understanding and drug development of SPN for the treatment of anemia.